2017
DOI: 10.18632/oncotarget.19650
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic hypomethylation and upregulation of matrix metalloproteinase 9 in Kawasaki disease

Abstract: BackgroundKawasaki disease (KD) is a type of febrile coronary vasculitis occurring in children. Some researchers have suggested that changes in genetic signatures, such as matrix metalloproteinases (MMPs), are critical markers for cardiovascular diseases. This study aims to provide a comprehensive survey of global DNA methylation levels and MMP transcripts of KD patients compared to control subjects.Materials and MethodsFor chips studies, we recruited a total of 18 KD patients, prior to receiving intravenous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…The three active DNA methyltransferases are DNMT1, DNMT3A, and DNMT3B, and three DNA demethylase, TET1-3, have been identified in mammals 7, 8. We have previously shown considerably increased mRNA expressions in toll-like receptors 9, hepcidin 10, 11, matrix metalloproteinases 12, inflammasome sensors of NOD-like receptors 13, and hypomethylation at the gene promoters of these genes, as well as that IVIG treatment can drastically alter these methylation patterns in the WBC cells of KD patients 9-14. Consistently, we have demonstrated that 87.8% of the most of the significant CpG markers between KD patients and controls are hypo-methylation of CpG markers by genome-wide screening on DNA methylation patterns with Illumina HumanMethylation450 (M450K) Bead-Chip microarray assay 15.…”
Section: Introductionmentioning
confidence: 91%
“…The three active DNA methyltransferases are DNMT1, DNMT3A, and DNMT3B, and three DNA demethylase, TET1-3, have been identified in mammals 7, 8. We have previously shown considerably increased mRNA expressions in toll-like receptors 9, hepcidin 10, 11, matrix metalloproteinases 12, inflammasome sensors of NOD-like receptors 13, and hypomethylation at the gene promoters of these genes, as well as that IVIG treatment can drastically alter these methylation patterns in the WBC cells of KD patients 9-14. Consistently, we have demonstrated that 87.8% of the most of the significant CpG markers between KD patients and controls are hypo-methylation of CpG markers by genome-wide screening on DNA methylation patterns with Illumina HumanMethylation450 (M450K) Bead-Chip microarray assay 15.…”
Section: Introductionmentioning
confidence: 91%
“…We have previously reported that IVIG administration significantly affects methylation pattern alterations in KD patients [17][18][19]. In short, DNA methylation can affect an inactive gene through DNA methyltransferases [20].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, higher levels of XLOC_006277 transcript were found in patients with KD that later developed CAA. After knockdown of XLOC_006277 with siRNA, KD or CAA-related markers, such as MMP-8 and MMP-9, were down-regulated 32,33 . Therefore, our data support the hypothesis that XLOC_006277 is critical for upstream signals that associate with CAA and is potentially a novel biomarker to predict CAA development.…”
Section: Discussionmentioning
confidence: 99%